Application of Simplex Lattice Design on the Optimization of Andrographolide Self Nanoemulsifying Drug Delivery System (SNEDDS) - Indrati, Oktavia; Martien, Ronny; Rohman, Abdul; Nugroho, Akhmad Kharis (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Background: Optimization of self-nanoemulsifying drug delivery system (SNEDDS) formulation is an important step to obtain optimal formulation with desired characteristics.Objective: This present study was aimed to utilize simplex lattice design in optimizing andrographolide SNEDDS.Method: Simplex lattice design was employed to optimize andrographolide SNEDDS in which component of SNEDDS was selected as the independent factor while the charactheristics of SNEDDS was used as the responses. Capryol-90, Kolliphor RH 40, and propylene glycol were selected as the oil, surfactant, and co-surfactant, respectively. Optimization of andrographolide SNEDDS formulation was based on their characteristics including emulsification time, droplet size, and drug content. The optimized SNEDDS formulation was evaluated for emulsification time, droplet size, drug content, and zeta potensial.Results: The emulsification time, droplet size, drug content, and zeta potensial of the optimized andrographolide SNEDDS was found to be 1.21±0.03 min, 44.02±0.67 nm, 6.69±0.08 mg/g, and -40.63±0.76 mV, respectively.Conclusion: This result suggested that simplex lattice design is a suitable for efficiently optimizing the formulation of andrographolide SNEDDS.